Seroprevalence of coxsackievirus A21 neutralizing antibodies in Yamagata, Japan, between 1976 and 2019; coxsackievirus A21 has rarely affected young children. Issue 6 (1st December 2021) - Tanaka, Waka; Komabayashi, Kenichi; Ikeda, Yoko; Aoki, Yoko; Itagaki, Tsutomu; Mizuta, Katsumi
Abstract: Although coxsackievirus A21 (CV‐A21) has been associated with an acute respiratory infection (ARI) as well as poliomyelitis‐like paralysis, reports of CV‐A21 detection have been quite limited both globally and in Japan. CV‐A21 strains were isolated from five sporadic pediatric cases with ARI in 2019 in Yamagata, Japan. Neutralizing antibodies (NT Abs) were then measured against CV‐A21 using sera collected in 1976, 1985, 1999, 2009, and 2019 in Yamagata, to clarify the longitudinal epidemiology of CV‐A21. The total Ab‐positive rate in each year was 15.2% (35/233), 10.7% (30/281), 14.3% (28/196), 3.1% (7/236), and 1.3% (3/226), respectively. Ab‐positive rates generally increased with age, especially between 1976 and 1999. Among the total Ab‐positive cases, the Ab titers were relatively low; 50 cases belonged to the 1:8–1:16, 40 to 1:32–1:64, 12 to 1:128–1:256, and 1 to 1:1024< groups, respectively. No Ab‐positive cases under the age of 10 were observed in any of the years analyzed. In conclusion, this study and previous works suggested that CV‐A21 is a unique enterovirus, which is not transmitted readily among young children but causes sporadic ARI cases mainly among those ≥15 years of age in the community. Highlights: This study suggested a unique characteristic of CV‐A21 that is not transmitted readily among children but rather causes ARI cases among those aged ≥ 15 years.